The construction of the Anwar-Najib debate in local newspapers / Sarah Nadiah binti Rashidi - Rashidi, Sarah Nadiah (2015)
The subject of a debate between Anwar Ibrahim and Najib Razak received extensive coverage in local newspapers in 2012. There is a stand-off in the representation of the debate between the mainstream newspapers and independent newspapers. This study aims to unveil the ideological construction of the debate between two opposing Malaysian leaders, Anwar Ibrahim and Najib Razak in local newspapers by analyzing how the mainstream newspaper and independent newspapers positively construct and legitimate the position of Self while negatively construct and de-legitimate the position of Other. This study focuses on twenty articles from mainstream newspapers and independent newspapers which are published from January 2012 to November 2012. The analysis of the articles follows the multi-disciplinary approach of Critical Discourse Analysis (CDA) with an adaptation of Wodak’s Discourse-Historical Approach (DHA). The discursive strategies employed to highlight the trends of Self and Other representation in the articles are analyzed through DHA’s analytical categories- Referential and Predicative strategies and Argumentation strategies. In addition, Quotation Patterns is included to validate the source of quotations found in the articles. The analysis reveals that the mainstream newspapers are found de-legitimizing the need for the debate through negative representation of Other (Anwar Ibrahim). The de-legitimisation of the debate is strengthened through the use of topos of disadvantage/ uselessness, topos of danger and threat and topos of culture. In contrast, the analysis on independent newspapers reveals that the need for the debate between Anwar Ibrahim and Najib Razak is legitimized also through negative representation of Other (Najib Razak). The legitimisation of the debate is reinforced through the use of topos of advantage/usefulness, topos of danger and threat and topos of culture. This study concludes that both the mainstream and independent newspapers rely heavily on the negative representation of Other in de-legitimising and legitimising the debate. The element of danger and threat, and culture can be constructed to either legitimate or de-legitimate the debate. Hence, despite reporting on the same topic, the Anwar-Najib debate, this study proves that language can be used to construct different ideologies to serve personal or political interest. Keywords: ideological construction, debate, mainstream newspapers, independent newspapers, discursive strategies